TINDAK PIDANA KORUPSI DI MASA PANDEMI COVID-19 - Eirene Dahlia Sidabutar; Limra G.M Nababan; Nasywa Yasmin Purba; Reh Bungana; Maulana Ibrahim (INTELIGENSIA MEDIA, 2023)
This paper discusses the corruption of the Minister of Social Affairs, Mr. Juliari Peter Batubara, on social assistance during the Covid-19 pandemic in Indonesia. During the covid-19 period there was a case of procurement of social assistance in the form of food packages for underprivileged citizens with a total of around Rp. 5.9 Trillion with a total of 272 contracts and implemented with two periods. Social assistance that has been managed by the ministry of social affairs is among the largest social assistance from the central government aimed at people affected by the corona virus, especially the poor. This research uses normative legal methods (doctrinal legal research). The method we use this time is a descriptive method by using a literature study, data collection techniques by examining the books used, literature, notes, and reports that have a relationship with the problem to be solved. The result of this study is that the corruption of social assistance funds has jolted the awareness of the public because the government allocates a budget that can be said to be quite large in handling Covid-19 cases for people affected by the pandemic. Where the funds come from the relocation of the budgets of institutions and ministries. if traced in the legal context, corruption is a product of weak law enforcement and public supervision of the practice of power from the state.